Transfusion medicine knowledge amongst specialist trainees at Groote schuur Hospital -using the BEST-TEST - Swart, Andries (Department of Anaesthesia and Perioperative Medicine, 2024)
Background: The primary aim was to assess transfusion medicine knowledge amongst specialist trainees at a South African tertiary hospital. Secondary aims included identifying shortcomings and describing differences in knowledge between subspecialty groups, comparing self-perceived knowledge against a known standard. Method: The Biomedical Excellence for Safer Transfusions test, or BEST test,1 was utilised to assess base knowledge amongst specialist trainees at a large tertiary hospital. It was administered as a secure online REDCap questionnaire sent to all eligible specialist trainees at Groote Schuur Hospital. Results: There were 104 responses of 241 eligible trainees, a response rate of 43.2%. The overall mean score for correct responses of the BEST test was 44.1% (median 40%), which is similar to studies using the BEST test in non-South African contexts. Most specialist trainees thought more transfusion training was needed (80.8% agreeing or strongly agreeing), and 70.2% rating it as very important. Self-perception of transfusion knowledge did not equate with the BEST test score. Compared to contexts outside Africa, respondents could better identify the risks of transfusion transmitted infections, but had difficulty with the administration of prophylactic platelets. The average scores for the BEST test did not markedly differ between specialties. Conclusion: Transfusion knowledge amongst specialist trainees in a large, tertiary hospital is deficient, and there is recognition amongst the specialist trainees that further training is required. However, the standard of transfusion knowledge in this institution is similar to other areas of the globe, which suggests that the global knowledge of transfusion medicine is inadequate.